Relationship between online social support and problematic internet use: a three-level meta-analysis - Miao Chao; Yufeng Wang; Jie Liu; Lijia Gu (BMC Psychology)
Abstract Despite the common advantages, such as increased life satisfaction and mental health, online social support (OSS), as a product of the digital age, has a potential negative influence on fostering problematic internet usage (PIU). Many studies have suggested that OSS is positively associated with PIU. The present study conducts a three-level meta-analysis to examine the extent to which OSS is correlated with PIU and analyzes various moderators to identify sources of research heterogeneity. After searching and screening the literature, we identified 26 studies, including 23,396 participants and 44 effect sizes, for analysis. Results showed that OSS was significantly and positively related to PIU. Moreover, moderator analyses showed that the association between OSS and PIU was moderated by the measurement of both OSS and PIU. We propose that individuals should be aware of the potential risks associated with OSS and proactively develop their offline social networks to establish a more robust social support system. This approach can potentially mitigate reliance on virtual social interactions while reducing the likelihood of problematic internet usage.